Sectoral impact of bank loans and labor: Lessons from Malaysia’s post-crisis years - Mohammed, Nurashikin; Khalid, Haniza (Global Academic Excellence, 2018)
This paper studies the relationship between bank loans and output of manufacturing and services sectors in Malaysia’s post-East Asian-crisis years. It is hypothesized that credit tightening and labor market instability that often characterize an economic meltdown can compromise a country’s output in the short run, at the very least. Our study which employed quarterly data between 1997 to 2016 showed that bank loans to manufacturing and services sector did indeed have a long-run and short-run impact on output of the said sectors. Hence, banking sector reforms that the government undertook immediately after the crisis to increase liquidity did prove to be critical in helping companies quickly recover lost ground as well as speed up the adoption of technology and innovation. By setting up complementary asset management companies, Danaharta Nasional Berhad and Pengurusan Danamodal Nasional Berhad in 1998, the government was able to remove banks’distraction with NPL and help improve their capital adequacy as well gave ailing companies opportunities to restructure their loans and continue with operations. Policy-wise this shows the crucial role of credit support in economic recovery strategies. On the other hand, labor played a much smaller role in determining manufacturing sector’s output compared to the services sector. This is consistent with changes in the labour market demand and supply that took place after the crisis years; including the employment of foreign labour and the improvement of local’s educational attainment). However, employment has a long-run relationship and short-run causality only with respect to the services sector, as local labor shift towards jobs in the services sector.